A Comprehensive Study of Copper Guanidine Quinoline Complexes: Predicting the Activity of Catalysts in ATRP with DFT1. Issue 38 (9th August 2016) - Rösener, Thomas; Bienemann, Olga; Sigl, Kerstin; Schopp, Nora; Schnitter, Fabian; Flörke, Ulrich; Hoffmann, Alexander; Döring, Artjom; Kuckling, Dirk; Herres‐Pawlis, Sonja
Abstract: Copper complexes of the hybrid guanidine ligands 1, 3‐dimethyl‐ N ‐(quinolin‐8‐yl)‐imidazolidin‐2‐imine (DMEGqu) and 1, 1, 3, 3‐tetramethyl‐2‐(quinolin‐8‐yl)‐guanidine (TMGqu) have been studied comprehensively with regard to their structural and electrochemical properties and their activity in atom transfer radical polymerization (ATRP). A simple analysis of the molecular structures of the complexes gives no indication about their activity in ATRP; however, with the help of DFT and NBO analysis the influence of particular coordinating donors on the electrochemical properties could be fully elucidated. With an adequate DFT methodology and newly applied theoretical isodesmic reactions it was possible to predict the relative position of the redox potentials of copper complexes containing DMEGqu and TMGqu ligands. In addition, predictions could be made as to whether the complexes of DMEGqu or TMGqu are more active in ATRP. Four new Cu I complexes were tested in standard ATRP reactions and kinetically investigated both in bulk and in solution. It could be proven that complexes featuring DMEGqu possess a lower redox potential and are more active in ATRP, although the tetramethylguanidine moiety represents the stronger donor. Abstract : The structural and electrochemical properties of Cu I X and Cu II X2 (with X=Br or Cl) complexes with the guanidine quinoline ligands DMEGqu and TMGqu were studied comprehensively and their activity in atom transfer radical polymerization (ATRP) was tested. The influence of even small structural changes on the electrochemistry and ATRP activity was predicted by means of DFT and isodesmic reactions. DMEGqu: 1, 3‐dimethyl‐ N ‐(quinolin‐8‐yl)‐imidazolidin‐2‐imine; TMGqu:1, 1, 3, 3‐tetramethyl‐2‐(quinolin‐8‐yl)‐guanidine.